Оцінювання концентрації регіонального ринку мультимодальних перевезень вантажів - Шандрівська, О. Є.; Shandrivska, O. (Видавництво Львівської політехніки, 2023)
Проаналізовано регіональний ринок мультимодальних перевезень (на прикладі Запорізької області) в частині ідентифікації конкурентних позицій транспортних підприємств та розподілу “ринкової влади” в сегменті вантажних перевезень між учасниками ринку мультимодальних перевезень. Здійснено оцінювання концентрації ринку мультимодальних перевезень Запорізької області із використанням індексу концентрації, індексу Лінда, індексу Херфіндаля–Хіршмана та індексу Джині. Ідентифіковано результати аналізу з позицій визначення рівня ринкової влади і конкурентної структури ринку мультимодальних перевезень вантажів. Ідентифіковано підприємство, яке формує “ядро” досліджуваного ринку: за аналітичними розрахунками це ПАТ “Укрзалізниця”. Визначено його роль у формуванні гостроти конкуренції на регіональному ринку мультимодальних перевезень. Окреслено напрями розвитку регіонального ринку мультимодальних перевезень із вичлененням та ідентифікацією рівнів конкурентної боротьби на ньому.

Purpose. This study aims to assess the regional market concentration of multimodal transport (on the example of the Zaporizhzhia region) and the distribution of "market power" in the freight transport segment between market participants in multimodal transportation. Design/methodology/approach. Authors in the article used the literature review method to substantiate the importance of identifying competition and distinguishing it among other related concepts in the development of regional markets for multimodal transportation by disclosing the specifics of their geographical location, availability of water resources, the establishment of logistics infrastructure, the volume of export-import flows of goods and other essential features in the process of an integrated approach to the formation of the regional market for multimodal transportation and, thus, to justify the relevance of the research topic. The market concentration of multimodal transport in the Zaporizhia region (using: concentration index, Lind index, Herfindahl–Hirschman index, and Gini index) allowed us to identify the company that forms the “core” of the market and determines its role in shaping the market. (According to analytical calculations, this includes PJSC “Ukrzaliznytsia”). The conducted analytical analyses allowed to suggest directions of development for the regional multimodal transportations market, particularly the identification of competition levels. Findings. Were proved the hypothesis concerning the need to eliminate the market monopolization of multimodal transportation in the Zaporizhzhia region and strengthen intra-industry and intersectoral competition in it. In particular, the development of the regional market of multimodal transportation should meet the industry needs and take into account the sectoral and regional peculiarities of all transport modes' functioning to develop multimodal technologies of cargo transportation. Practical implications. This study's results are of interest to multimodal transport market operators and cargo owners who are interested in the active implementation of logistics concept into regions development, the practical implementation of which should be, in particular, the intensification centers of cargo handling. These centers are entrusted with the functions of transshipment of goods from one to other transport modes, the allocation of links in the integrated transport chain, the formation of economic development centers in certain regions. This involves, in particular, the construction of multimodal regional clusters. In this way, it is expected to increase the involvement of cargo flows in the regions, the development (intra-industry – between different participants in the transportation process of goods; intersectoral – between different modes of transport in the area; commodity competition – under the conditions of transition to cargo substitute transportation; geographical – in terms of goods delivery by an alternative route); growth of employment in the freight sector and other related industries, etc. The evaluation results of the development of multimodal cargo transportation can be taken into account by the Coordination Council for Logistics at the Ministry of Infrastructure of Ukraine to form strategic foundations for the country’s logistics system development. The components of such a strategy should relate to the improvement of multimodal freight transport, the optimization of regional and interregional transport cooperation, the progress of the management of logistics supply chains; increasing the profitability of the transport sector, the formation of economic benefits from the trade development, the national economy cooperation, and development. Originality/value. Assessing the concentration of regional markets will provide an analytical basis in the process of forming a mechanism to ensure the efficiency of multimodal freight comprehensively and minimize interregional asymmetries: the levels of cargo flow by the stated needs of consumers; state of transport and logistics infrastructure; provision of all types of transportation method, service levels, etc.
Assessment of the regional market concentration of multimodal cargo transportation
Keywords: ринок мультимодальних перевезень вантажів; ринкова частка; індекс концентрації; індекс Лінда; індекс Херфіндаля–Хіршмана; індекс Джині; концентрація ринку; види конкуренції; multimodal transportation market; market share of enterprises; concentration index; Linda index; Herfindahl–Hirschman index; Gini index; market concentration; types of competition; 656.078.1